1998
DOI: 10.1007/bf03012142
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia following appendicectomy — the value of peritoneal bupi-vacaine

Abstract: Analgesia following appendicectomy-the value of peritoneal bupivacainePurpose: Peritoneal inflammation is an important feature in many patients presenting with appendicitis. The contribution of peritoneal nerve fibres to pain experienced after appendicectomy has received little attention. Method: In this prospective double blind randomized study a consecutive series of 60 patients undergoing appendicectomy for suspected appendicitis were enrolled. A dose of 1.5 mg-kg-' bupivacaine 0.5 % was used. Group one pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In another study, 17 10 ml 2% lidocaine was administered peritoneally, and it was reported that this too provided effective analgesia. Some other studies have shown similar results 16–23 …”
Section: Discussionsupporting
confidence: 67%
“…In another study, 17 10 ml 2% lidocaine was administered peritoneally, and it was reported that this too provided effective analgesia. Some other studies have shown similar results 16–23 …”
Section: Discussionsupporting
confidence: 67%
“…Pain was assessed in seven RCTs 34–40 . However, only six trials compared IPLA with placebo or no IPLA as one trial was a dose finding study 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Other authors have emphasized the importance of peritoneal irritation in postoperative pain rather than pain from the abdominal wall musculature. A randomized trial comparing combined bupivacaine infiltration to the peritoneum and the skin compared with skin alone after appendicectomy did show lower pain scores at 30 min and lower analgesic use in the first 24 h postoperatively [5].…”
Section: Discussionmentioning
confidence: 99%